Endemic caseous lymphadenitis in a wild Caprinae population. (22nd April 2017) - Varela‐Castro, L.; Lara‐Vergara, J.; Ortega, N.; Salinas, J.; Colom‐Cadena, A.; Lavín, S.; Tizzani, P.; Velarde, R.; Serrano, E.; Mentaberre, G.
Abstract : Between 2010 and 2013, an outbreak of caseous lymphadenitis (CLA) occurred in a captive stock of Iberian ibexes ( Capra pyrenaica, Schinz 1838) maintained for conservation purposes in the National Game Reserve 'Ports de Tortosa i Beseit' (PTB), northeastern Spain. The aim of this study was to assess the CLA status in the free‐ranging donor population of ibexes. An ELISA test to detect antibodies to CLA was performed in 360 hunter‐harvested ibexes between 2007 and 2013. A spatial analysis and recursive partitioning approaches with regression tree models were used to explore CLA‐associated risk factors. Nineteen per cent of ibexes had antibodies to CLA. Significant differences in seroprevalence were observed among game management areas but no clear trends of CLA occurrence were observed over the study period. Ibexes from areas of higher population density and living close to aggregation points displayed a higher probability of testing positive to CLA. These results suggest that CLA is endemic in the Iberian ibex population inhabiting PTB and density‐dependent risk factors. To the best of our knowledge, this is the first record of CLA maintenance in a free‐ranging wild Caprinae population.